Efficacy and safety of the new biopsy strategy combining 6-core systematic and 3-core MRI-targeted biopsy in the detection of prostate cancer: Study protocol for a randomized controlled trial - Zhang, Chichen; Tu, Xiang; Dai, Jindong; Xiong, Xingyu; Cai, Diming; Yang, Ling; Zhang, Mengni; Qiu, Shi; Lin, Tianhai; Liu, Zhenhua; Yang, Lu; Wei, Qiang (Frontiers in Surgery, 2023)
Background Recent EAU guideline strongly recommended combined targeted biopsy (TBx) with systematic biopsy (SBx) for biopsy naïve patients with suspected multiparametric magnetic resonance imaging (mpMRI) lesions; However, the clinical goal is to find out how to determine the optimal SBx and TBx cores for biopsy in order to maximize the detection of csPCa and minimize the associated defects. This study aims to assess the efficacy and safety of the new biopsy strategy combining 6-core systematic and 3-core MRI- TBx compared to 12-core systematic and 3-core MRI-TBx strategy. Methods This is a single-center, prospectively randomized controlled clinical trial. 280 men meeting inclusion criteria will be recruited and will be randomly allocated to either 6-core systematic plus 3-core MRI-TBx group (Group A) or 12-core systematic plus 3-core MRI-TBx group (Group B). The primary outcome compares the detection rate of PCa and clinically significant prostate cancer(csPCa) between group A and group B. The secondary outcomes compare the participant-reported pain score immediate post biopsy using pain measurement scale; proportion of men with post-biopsy complications and adverse events (Time frame: 7 days post biopsy, 30 days post biopsy); proportion of the men who undergo radical prostatectomy and have cancer upgraded histopathology from the biopsy to the radical prostatectomy. Results and Discussion A new biopsy strategy should be developed with the goal of minimizing procedure invasion, our study will provide the results of efficacy and safety of the new biopsy strategy (6-core systematic and 3-core MRI-TBx) in biopsy naïve men with suspicious mpMRI lesion in comparison with 12-core systematic and 3-core MRI-TBx. Trial registration Chinese Clinical Trial Registry, ChiCTR2200056437; http://www.chictr.org.cn/edit.aspx?pid=151413&htm=4